2021
DOI: 10.3390/biom11020243
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharides Derived from Tramesan: Their Structure and Activity on Mycotoxin Inhibition in Aspergillus flavus and Aspergillus carbonarius

Abstract: Food and feed safety are of paramount relevance in everyday life. The awareness that different chemicals, e.g., those largely used in agriculture, could present both environmental problems and health hazards, has led to a large limitation of their use. Chemicals were also the main tool in a control of fungal pathogens and their secondary metabolites, mycotoxins. There is a drive to develop more environmentally friendly, “green”, approaches to control mycotoxin contamination of foodstuffs. Different mushroom me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Additionally, Tramesan was also found to have agricultural applications. It can be used as a natural alternative to crop protection chemicals for controlling the mycotoxins produced by Aspergillus flavus and A. carbonarius [183]. Finally, this exopolysaccharide inhibits the growth of wheat pathogens, Zymoseptoria tritici and Parastagonospora nodorum [184].…”
Section: Macrofungal β-Glucansmentioning
confidence: 99%
“…Additionally, Tramesan was also found to have agricultural applications. It can be used as a natural alternative to crop protection chemicals for controlling the mycotoxins produced by Aspergillus flavus and A. carbonarius [183]. Finally, this exopolysaccharide inhibits the growth of wheat pathogens, Zymoseptoria tritici and Parastagonospora nodorum [184].…”
Section: Macrofungal β-Glucansmentioning
confidence: 99%
“…Many strategies have been predominantly based on the use of chemical compounds (pesticides and fungicides). The number of chemicals that were applied in the prevention of fungal growth and/or mycotoxin control has been banned by authorities [ 13 , 14 , 15 ]. This, together with rising environmental awareness of the population, led to an increase in the research for new more environmentally friendly strategies in mycotoxin control.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 20 years, different research confirmed that mushroom polysaccharides could represent a valid tool in mycotoxin control [ 22 , 23 , 24 , 25 , 26 ]. The most studied inhibiting effects of mushroom metabolites are those made with Lentinula edodes [ 22 ] and Trametes versicolor [ 15 , 24 , 25 ] using lyophilized culture filtrates. Moreover, Scarpari and collaborators [ 25 ] were able to identify the active principles produced by T. versicolor , which was an exopolysaccharide released in its culture filtrate, called tramesan.…”
Section: Introductionmentioning
confidence: 99%
“…Fungal polysaccharides, including exopolysaccharides (EPS) and endopolysaccharides, isolated from fruiting bodies, cultured mycelia, and cultured broth, exhibit a variety of biological properties, including antioxidant, antiviral, antitumor, and immunomodulatory activities [ 12 , 13 , 14 ]. An extracellular polysaccharide of Rhizopus nigricans inhibits the proliferation of colon cancer cells by relieving immunological inflammation in mice [ 15 ].…”
Section: Introductionmentioning
confidence: 99%